The effect of a feruloyl esterase producing inoculant along with mechanical treatment prior to ensiling on fibre digestibility of grass silage - Haile, Kiros Kelkay (SLU/Dept. of Animal Nutrition and Management (until 231231), 2019)
Plant fibre is the main portion of dairy cattle diets. It is also important in maintaining health and proper function of the rumen. However, digestibility of fibre is relatively low, and, in most cases, it is not more than 60%. In cell walls of grasses and cereals, lignin and hemicellulose are connected, forming a matrix. This matrix coats the cellulose and this overall structure of fibre is considered as the key reason for a low fibre digestibility. The main binding component between lignin and hemicellulose is ferulic acid. Feruloyl ester-ases (FAEs) are enzymes that can cleave the ferulic acid linkages between lignin and hemicellulose. The objective of the study was to investigate the effect of a FAE producing inoculant (FAEI) along with physical treatment prior to ensiling on digestibility of silage fibres. Ryegrass and meadow fes-cue samples were collected during autumn 2018, chopped and thereafter fro-zen (-20oC) until the trial was started. At the time of the trial (2019), the grass samples were thawed and wilted in room temperature until the dry matter (DM) content reached ~35%. Six treatments, in triplicate, were compared for the effect on neutral detergent fibre digestibility (NDFD) of the silages. The treatments were untreated control, inoculation with Lactobacillus buchneri LN4017, Mild, Harsh, inoculation plus Mild and inoculation plus Harsh. The Mild treatment was pounding grass samples with a metal rod and the Harsh treatment was mincing grass samples with a meat mincer. After application of treatments, forages were ensiled in glass silos (100 mL) for 48-49 d. The NDFD of silage was assessed by a 96-h in vitro incubation with buffered ru-men liquid. The pH of ryegrass and meadow fescue silages were on average 4.4 and 4.5, respectively. In both trials, inoculation increased silage pH and mechanical treatment reduced silage pH. The FAEI alone or along with me-chanical treatment had no effect on NDFD of silages.